2022
DOI: 10.2478/pjph-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine addiction – a health problem in adolescents in a neurobiological context

Abstract: Smoking is one of the leading causes of death which can be prevented in the developed countries. Smoking begins mainly in adolescence. Smoking in early adolescence is known to be associated with an increased risk of later addiction. Also the growing popularity of e-cigarettes, which attract young people with a variety of flavors, and are still little associated with harmful effects on health, unlike regular cigarettes. Exposure to nicotine in young people can affect learning, memory and attention, and lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Nicotine and other tobacco metabolites can be present in the human gastrointestinal tract, affecting its secretions and metabolism and the intestinal microbiome. For instance, nicotine relaxes smooth muscle and increases pepsin secretion . Previous studies have shown that smoking generates reactive oxygen species (ROS) in the blood, leading to oxidative stress and activation of JNK and p38 signaling .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine and other tobacco metabolites can be present in the human gastrointestinal tract, affecting its secretions and metabolism and the intestinal microbiome. For instance, nicotine relaxes smooth muscle and increases pepsin secretion . Previous studies have shown that smoking generates reactive oxygen species (ROS) in the blood, leading to oxidative stress and activation of JNK and p38 signaling .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, nicotine relaxes smooth muscle and increases pepsin secretion. 57 Previous studies have shown that smoking generates reactive oxygen species (ROS) in the blood, leading to oxidative stress and activation of JNK and p38 signaling. 58 Smoking also alters the mucin composition of the gut and cellular tight junction molecules, in addition to causing local acid−base imbalances in the gut.…”
Section: Microbial Biomarker Discovery By Lefsementioning
confidence: 99%